2015
DOI: 10.1080/00224499.2015.1063575
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Development of Sexual Excitation and Inhibition Through the Life Course: Preliminary Findings from a Representative Study in Flanders

Abstract: The dual control model proposes that there are individual differences in the propensity for sexual excitation and sexual inhibition. Research to date has considered the effect of age on these traits as a simple linear effect, and studies examining gender differences in age effects are lacking. There are, however, indications that the associations of age with excitation and inhibition are nonlinear and that there might be gender differences in these associations. The aim of this study was to examine how these t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…Largest gender-differences were found concerning relationship importance ( d = 0.72), SES1 ( d = 0.58), arousability ( d = 0.56), inhibitory cognitions ( d = 0.51), SIS2 ( d = 0.46), SES2 ( d = 0.44), and SIS1 ( d = 0.38). This finding is in line with previous studies that reported such gender-differences based on observed scores, not latent means [ 12 , 21 , 24 ]. These results are also in accordance with the dual control model’s assumptions [ 2 ] and can be explained by evolutionary mechanisms [ 61 ] as well as differences in social learning [ 62 ].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Largest gender-differences were found concerning relationship importance ( d = 0.72), SES1 ( d = 0.58), arousability ( d = 0.56), inhibitory cognitions ( d = 0.51), SIS2 ( d = 0.46), SES2 ( d = 0.44), and SIS1 ( d = 0.38). This finding is in line with previous studies that reported such gender-differences based on observed scores, not latent means [ 12 , 21 , 24 ]. These results are also in accordance with the dual control model’s assumptions [ 2 ] and can be explained by evolutionary mechanisms [ 61 ] as well as differences in social learning [ 62 ].…”
Section: Discussionsupporting
confidence: 93%
“…As the likelihood for sexual dysfunctions such as erectile problems or low desire increases with age [ 67 ], concerns or worries about sexual performance may become more salient. The age-related pattern is in line with the one other study that used the SIS/SES-SF in a population-based representative sample [ 14 , 21 ]. Their analysis, however, revealed an interaction between the effect of age and gender on SIS1, with men showing a linear increase in SIS1 with age, and women showing a u-shaped pattern with highest values reported between 40 and 50 years of age.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations